2010
DOI: 10.1161/circresaha.110.220970
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4-Mediated Bone Marrow Progenitor Cell Maintenance and Mobilization Are Modulated by c-kit Activity

Abstract: Rationale: The mobilization of bone marrow (BM) progenitor cells (PCs) is largely governed by interactionsbetween stromal cell-derived factor (SDF)-1 and CXC chemokine receptor (CXCR)4. Ischemic injury disrupts the SDF-1-CXCR4 interaction and releases BM PCs into the peripheral circulation, where the mobilized cells are recruited to the injured tissue and contribute to vessel growth. BM PCs can also be mobilized by the pharmacological CXCR4 antagonist AMD3100, but the other components of the SDF-1-CXCR4 signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 51 publications
3
62
1
Order By: Relevance
“…Furthermore, prolonged SCF treatment of human CD34 + HSPCs increases CXCR4 surface expression, resulting in their enhanced homing potential toward the BM of recipient NOD/SCID mice (51). Additionally, W/Wv mice, having defective cKit kinase activity, do not mobilize in response to AMD3100 administration and demonstrate low expression of surface CXCR4 on HSPCs (26). Nevertheless, the major difference between these GSK3β pathway findings (days or constant deficiency) and our findings (hours) is noted in the CXCR4 expression-dependent effects versus the CXCR4 expression-independent effects, respectively.…”
Section: Scf Enhances Hspc Migration Via Gsk3βcontrasting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, prolonged SCF treatment of human CD34 + HSPCs increases CXCR4 surface expression, resulting in their enhanced homing potential toward the BM of recipient NOD/SCID mice (51). Additionally, W/Wv mice, having defective cKit kinase activity, do not mobilize in response to AMD3100 administration and demonstrate low expression of surface CXCR4 on HSPCs (26). Nevertheless, the major difference between these GSK3β pathway findings (days or constant deficiency) and our findings (hours) is noted in the CXCR4 expression-dependent effects versus the CXCR4 expression-independent effects, respectively.…”
Section: Scf Enhances Hspc Migration Via Gsk3βcontrasting
confidence: 59%
“…Catecholamines by themselves directly augment the motility of human HSPCs (25). Interestingly, cKit (also termed CD117), which serves as a marker for HSPCs, and its ligand SCF (also termed Kit ligand), are involved in human and murine HSPC motility (26)(27)(28)(29)(30), pointing to a signaling pathway that uniquely regulates the migration of immature hematopoietic cells over mature leukocytes. Moreover, mutant mice with low serum levels of IGF-1 exhibit markedly increased numbers of circulating HSPCs with normal numbers of mature white blood cells (WBCs) (31), pointing to another mechanism by which the egress of immature hematopoietic cells is preferentially regulated.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28]30,31 Given the close association between CXCR4 signaling and EPCs targeted repair for endothelium, we hypothesized that disturbance in CXCR4 signaling is related to the impaired EPC function in the elderly. We show that SDF-1-induced phosphorylations of CXCR4 and JAK-2 are significantly lower in EPCs from the elderly than in EPCs from the young.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence to show that CXCR4 is a key regulator of homing and retention of EPCs at the sites of injured artery, [26][27][28] suggesting that an impaired CXCR4 signaling may lead to a decrease in endothelial repair capacity of EPCs. Our recent study indicated that impairment of CXCR4-mediated Janus kinase 2 (JAK-2) phosphorylation is involved in the aged-related reduction in endothelialization capacity of EPCs 29 ; however, the role of CXCR4 phosphorylation in the regulation of CXCR4/JAK-2 signaling is unknown.…”
mentioning
confidence: 99%
“…108 108 The evidence from this study suggests that SDF-1-CXCR4 signaling upregulates c-kit activity at the protein level, and that the loss of CXCR4 receptor resulted in decreased c-kit activity.…”
Section: Knockdown Construct Reduces In Vitro Mrna and Cell Surface Ementioning
confidence: 80%